2009
DOI: 10.1074/jbc.m807643200
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Dephosphorylation of the Syndecan-1 PDZ Binding Domain Regulates Syntenin-1 Recruitment

Abstract: Heparan sulfate proteoglycan receptor syndecan-1 interacts with the carboxyl-terminal LG4/5 domain in laminin 332 (alpha3LG4/5) and participates in cell adhesion and spreading. To dissect the function of syndecan-1 in these processes, we made use of a cell adhesion model in which syndecan-1 exclusively interacts with a recombinantly expressed alpha3LG4/5 fragment. Plating HT1080 cells on this fragment induces the formation of actin-containing protrusive structures in an integrin-independent manner. Here we sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 58 publications
2
55
0
Order By: Relevance
“…An alternative possibility is that the interaction between the syndecan and the integrin is not direct but is mediated by a PDZ-domain protein, such as syntenin. This possibility would seemingly be supported by recent work showing that Sdc1 binding to syntenin is promoted upon epithelial cells binding to the LG4,5 domain of LN332 (39). However, silencing syntenin expression in the A431 cells with RNA interference has no effect on the integrin signaling mechanism.…”
Section: Tsupporting
confidence: 58%
See 1 more Smart Citation
“…An alternative possibility is that the interaction between the syndecan and the integrin is not direct but is mediated by a PDZ-domain protein, such as syntenin. This possibility would seemingly be supported by recent work showing that Sdc1 binding to syntenin is promoted upon epithelial cells binding to the LG4,5 domain of LN332 (39). However, silencing syntenin expression in the A431 cells with RNA interference has no effect on the integrin signaling mechanism.…”
Section: Tsupporting
confidence: 58%
“…Engagement of LG4,5 enhances keratinocyte cell spreading and migration (36 -38), which probably traces to Sdc1 because of its high expression on keratinocytes. Interestingly, it is proposed that this is regulated by phosphorylation of the C2 region of the syndecan cytoplasmic domain and its interaction with the PDZ domain of syntenin (39). In addition, Sdc1 has been shown to interact with the ␥2 chain of LN332 (40).…”
mentioning
confidence: 99%
“…Where information is available, key differences are seen between Sdc1 engaging the ␤4 integrin, syntenin, and Tiam-1. Binding to syntenin relies on an XFXA motif and is disrupted if Tyr (P Ϫ1 ) is phosphorylated (54,55,70). Binding to the Tiam-1 PDZ domain appears to rely on KXEXFXX composed partly of the C2 region (EFYA) and KXE from the syndecan V region.…”
Section: Blotmentioning
confidence: 99%
“…Note that the EFYA sequence that comprises the C2 region has been shown to be a PDZ domainbinding motif, depending on Phe (P Ϫ2 ) and Ala (P 0 ) (54). Tyr at P Ϫ1 can be mutated to Phe or Ala, but it cannot be phosphorylated without disrupting PDZ domain binding (54,55). To test whether ␤4 integrin binding obeys these same rules, we tested peptides in which the Phe or Tyr is mutated, or Tyr is phosphor- …”
Section: Syndecans Regulate Her2-/egfr-specific Integrin Activationmentioning
confidence: 99%
“…When the cells contact with the extracellular matrix (ECM), extended filopodia binds to ECM through integrins and mediates the formation of focal adhesion, which is a power source of cell migration (Meurice et al, 2010). Mda-9/syntenin could remodel the actin cytoskeleton, induce the formation of a variety of plasma membrane structures including goffer, lamellipodia and neurite-like structure in neurons and different types of tumor cells, indicating it may play a role in tumor cell adhesion and migration (Zimmermann et al, 2001;Hirbec et al, 2005;Sulka et al, 2009). Some clinical trials have confirmed that mda-9/syntenin was overexpressed in melanoma, metastatic breast cancer and gastrointestinal tumors and the level of mda-9/syntenin was closely correlated with the tumor malignant grades and tumor metastasis (Koo et al, 2002;Helmke et al, 2004;Boukerche et al, 2005;Boukerche et al, 2008).…”
Section: Discussionmentioning
confidence: 99%